Analisis Ekonomi dan Break Event Point Pada Pembuatan Tepung Maggot dengan Memanfaatkan Limbah Ternak dan Limbah Rumah Tangga - Anang Widigdyo; Rani Arifah Normawanti; Adiguna Sasama Wahyu Utama (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2023)
Maggot is a type of insect that has a high nutritional content that can be used as a feed ingredient. Maggot's characteristics as a decomposer can provide solutions to environmental problems, such as the problem of chicken manure and household waste. These two media have proven to be used as media for Maggot production, so that bioconversion or recycling of organic waste is formed, as well as a circular economy because the Maggot produced can be used as a chicken feed ingredient. This study attempts to analyze from an economic perspective whether Maggot production for feed ingredients is more effective than manufactured feed, including analyzing the required production breakeven point